A PRACTICAL ACCOUNTING COURSE FOR NON-COMMERCE STUDENTS. - van Voorhis, Robert H. (The Accounting Review, 1954)
Abstract A careful review of the course outlined above discloses that much of the material included in the typical accounting survey course is covered. In spite of its novel beginning, it ultimately provides the student with an orthodox picture of double entry bookkeeping. By the time section nine is reached, we are using the accrual basis of accounting, with four common special journals, plus a general journal, a complete general ledger, and controlling accounts and subsidiary ledgers. Inventory problems and accounting for notes and interest are explained. Payroll preparation and employee earnings records have previously been covered, as have property taxes. Sales tax, use tax, privilege license tax, and the individual income tax are covered in subsequent sections. The balance sheet and statement of income and expense have been shown in several uses. Methods of analyzing published corporate reports are explored, and governmental financial problems and reports are considered. In addition to this coverage of traditional material, our course has the advantage of offering specific helps in some of the more common financial and record keeping problems an individual is likely to meet. Designed as it is for students in fields other than commerce, it may provide theft only exposure to the subjects of credit, insurance, and taxation. While coverage of these matters is by no means comprehensive, it should serve to answer the more general questions and to indicate the point beyond which professional counsel should be obtained. As noted above, perhaps the most significant feature of the course is its approach to accounting instruction. Without preliminary discussion, the student begins to record data in a combined cash journal. Through this approach, the student finds himself at the very outset keeping a practical record whose immediate usefulness to him in his present situation he can readily understand.